Preoperative education reduces preoperative anxiety in cancer patients undergoing surgery: Usefulness of the self-reported Beck anxiety inventory - Lemos,Marilia F. (2019)
Abstract Background and objectives: Preoperative instruction is known to significantly reduce patient anxiety before surgery. The present study aimed to investigate the effects of preoperative education on the level of anxiety of cancer patients undergoing surgery using the self-reported Beck anxiety inventory. Methods: This study is a short-term observational study, including 72 female patients with a diagnosis of endometrial cancer who were scheduled to undergo surgical treatment under general anesthesia. During the pre-anesthetic consultation 15 days before surgery, one group of patients (Group A, n = 36) was given comprehensive information about their scheduled anesthetic and surgical procedures, while the other group of patients (Group B, n = 36) did not receive any information pertaining to these variables. The Beck anxiety inventory, blood pressure and heart rate were evaluated before and after the preoperative education in Group A. In Group B, these parameters were evaluated at the beginning and at the end of the consultation. Results: The hemodynamic values were lower in the group that received preoperative education, in comparison with the group that did not receive preoperative education. Educating the patients about the procedure resulted in a reduction in the levels of anxiety from mild to minimum, whereas there was no change in the group that did not receive the preoperative education. This latter group kept the same level of anxiety up to the end of pre-anesthetic consultation. Conclusions: Patient orientation in the preoperative setting should be the standard of care to minimize patient anxiety prior to surgery, especially for patients with cancer.